The spiritual factors influencing health-seeking behaviour among the Seventh Day Adventist group members in Tshwane Gauteng Province - Bila, Nontembeko (University of Pretoria, 2022)
Mini Dissertation (MSW (Health Care))--University of Pretoria, 2021.